Does ESG Matter across the CLC? Evidence from Trade Credit in ASEAN Non Cyclical Firms - Setio, Ellen Chaecaria; Wulandari, Permata (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Trade credit financing is an important source of short-term financing. Previous studies suggest that firms’ financing behavior may vary across corporate life cycle stages, while environmental, social, and governance performance may function as a signal of credibility and reduce information asymmetry between firms and suppliers. This study aims to examine the effect of CLC on TCF and to test whether ESG performance moderates this relationship. It was hypothesized that CLC stages affect TCF and that ESG performance strengthens the relationship between CLC and TCF. This study used panel data from non-cyclical listed firms in ASEAN during the 2016–2024 period. CLC was classified based on cash flow patterns, while TCF was measured using accounts receivable, accounts payable, and net trade credit as an alternative proxy. ESG performance was measured using ESG scores. Panel regression analysis was conducted after model selection tests, including Chow, Lagrange multiplier, and Hausman tests. Firm-level control variables were also included. The findings indicate that CLC and ESG performance do not have a consistent direct effect on accounts receivable, accounts payable, or net trade credit. However, the moderating effect of ESG performance is found to be significant in specific life cycle stages. In the main model, the interaction between decline stage and ESG performance shows a positive and significant effect on accounts payable. In the alternative model using net trade credit, the interaction effects are negative and significant in the introduction and decline stages. The results suggest that ESG performance does not uniformly increase TCF, but its role depends on the firm’s life cycle stage and the trade credit proxy used. These findings support the view that trade credit decisions are shaped by firm-specific conditions, credibility signals, and financing needs rather than by life cycle or ESG performance alone.